(untitled) (Global Journal of Human-Social Science, 2023)
Religion governance and politics as well as related topics such as human rights justice and so on have historically caused many of the world s most significant conflicts and they continue to do so because these issues are often the most fundamental in the structure of a society To gain a military advantage parties to armed conflicts have polluted water burned crops cut down forests poisoned soils and killed animals over the years A variety of context factors particularly socioeconomic conditions governance and political factors interact and play a key role in translating climate change into conflict risks The present unrest all over the world risks putting more than half of the countries into a crisis of health economy and social safety which is the biggest threat to human civilization The security and safety of healthcare facilities workers and supply lines remain paramount concerns along with access to health services technology and innovation